2022
DOI: 10.1007/s10570-022-04430-y
|View full text |Cite
|
Sign up to set email alerts
|

Durable and high-efficiency casein-derived phosphorus-nitrogen-rich flame retardants for cotton fabrics

Abstract: A casein derivative (CADP) was synthesized using casein, which is bifunctional containing both -P=O(O -NH 4 + ) 2 reactive groups and -P(=O)-O-C-groups, and the durable ame-retardant cotton fabrics were successfully prepared by CADP. The -P=O(O -NH 4 + ) 2 reactive groups allowed CADP to be rmly grafted onto cellulose. The -P(=O)-O-C-groups made ame-retardant cotton fabrics more resistant to soaping and improved its durability. The modi cation by 40% CADP increased the limited oxygen index value (LOI) of cotto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The peak due to P=O is centered at 1250 cm −1 , while the peak centered at 884 cm −1 is associated with the P-O bond. Furthermore, the presence of the amide group can be confirmed by the peaks at 1624 cm −1 (amide vibration) and 1528 cm −1 (amide vibration), which are evidence of flame retardant treatment on the cotton fabric [46]. Moreover, in the case of sample A and sample 23, there is a major shift of FTIR spectra in the wavenumber range of 400 cm −1 to 500 cm −1 , which can be attributed to the presence of ZnO NPs on the cotton fabric.…”
Section: Ftir Analysismentioning
confidence: 91%
“…The peak due to P=O is centered at 1250 cm −1 , while the peak centered at 884 cm −1 is associated with the P-O bond. Furthermore, the presence of the amide group can be confirmed by the peaks at 1624 cm −1 (amide vibration) and 1528 cm −1 (amide vibration), which are evidence of flame retardant treatment on the cotton fabric [46]. Moreover, in the case of sample A and sample 23, there is a major shift of FTIR spectra in the wavenumber range of 400 cm −1 to 500 cm −1 , which can be attributed to the presence of ZnO NPs on the cotton fabric.…”
Section: Ftir Analysismentioning
confidence: 91%
“…Our review of the literature regarding FR yarns and fabrics revealed that most studies were concerned with imparting flame resistance to fabrics during finishing processes. [5][6][7][8][9][10][11][12][13][14][15][16][17] This was followed by a number of studies that investigated the properties of the yarns and fabrics made from FR fibers. [18][19][20][21][22][23][24] A small number of studies examined the burning behaviors of fabrics produced from inherently FR meta-aramid and para-aramid fibers, or from their different blends.…”
mentioning
confidence: 99%